The emerging role of nimotuzumab in the treatment of non-small cell lung cancer - Boland, William (Dove Medical Press, 2010)
Current non-small cell lung cancer (NSCLC) chemotherapy and radiotherapy regimens, although showing definite survival benefit, still leave patients with a disappointing 15% 5-year overall survival rate. Because of the need to improve traditional outcomes, research has focused on identifying specific tumorigenic pathways that may serve as therapeutic targets. The most successful strategies to date are those aimed at the epidermal growth factor receptor (EGFR), which is found to be upregulated in 40%–80% of NSCLC. Several tyrosine kinase inhibitors and monoclonal antibodies (mAbs) have been developed that inhibit the EGFR receptor and have demonstrated clinical benefit in trials as single agents and in combination regimens. Here we discuss one such agent, the mAb nimotuzumab, the background of its development, its clinical experience in NSCLC thus far, and the rationale for expanding its use to other NSCLC treatment settings.